Successful Reversal of Bradycardia and Dyspnea With Aminophylline After Ticagrelor Load. (February 2018) - Minner, Sarah A.; Simone, Pamela; Chung, Benjamin B.; Shah, Atman P.
A 69-year-old male underwent elective percutaneous coronary intervention requiring placement of a drug-eluting stent to the first obtuse marginal artery. Four hours following the administration of a ticagrelor loading dose, he developed dyspnea and sinus pauses. Aminophylline was administered and resulted in immediate and sustained symptom resolution. Ticagrelor has been associated with dyspnea and bradyarrhythmias, both attributed to increased adenosine exposure. Ticagrelor inhibits reuptake of intracellular adenosine. Adenosine antagonists aminophylline and theophylline have been utilized to reverse the effects of adenosine and may relieve adenosine-mediated adverse effects induced by ticagrelor therapy. Aminophylline may be considered for reversal of dyspnea and bradyarrhythmia associated with ticagrelor therapy through alterations in adenosine exposure.